2022-LBA-714-ESGO Full-thickness partial diaphragm resection using an Endo GIA vascular stapler in patients with advanced-stage ovarian cancer: an institutional series. (27th October 2022) - Huber, Daniela; Fournier, Ian; Nef, James; Christodoulou, Michel; Seidler, Stéphanie; Besse, Valérie; Hurni, Yannick
Abstract : Introduction: Patients with advanced-stage ovarian cancer frequently present with peritoneal carcinomatosis with a diaphragmatic involvement. During cytoreduction surgeries, deep infiltrating nodules require diaphragmatic full-thickness resections (DFTRs). These procedures involve opening the pleural cavity, often requiring a chest drain, and are associated with a high rate of postoperative complications. We present a novel technique to perform DFTRs using a surgical stapler without opening the pleural cavity, and we report our preliminary results. Methods: Analysis of consecutive patients undergoing full thickeness diahragmatic resection using an EndoGIA vascular stapler by a single surgical team since January 2018. Results: Fifteen patients underwent cytoreductive surgeries with S-DFTRs. The median operative time was 300 (114 – 547) minutes. Cytoreduction was considered complete in all cases. Concomitant contralateral diaphragmatic peritoneal stripping was performed in 5 cases (33.3%) and was associated with a conventional DFTR in 1 case (6.7%). Pleural effusion was observed in 9 patients (60.0%), and 4 (26.7%) required a postoperative pigtail catheter thoracostomy. Three patients (20.0%) required catheter placement (ipsilaterally to the S-DFTR) and 2 patients (13.3%) required catheters on the contralateral hemithorax. Pulmonary embolism and pneumonia were both observed once (6.7%). The median hospitalization length was 14 (5 – 36) days. During the follow-up, 6 patients (40.0%) had a recurrence, but none involved the pleura or the diaphragm. Conclusions: This technique appears as a safe and easy method for performing diaphragmatic resections and could reduce postoperative complications.